2016
DOI: 10.1002/crat.201600207
|View full text |Cite
|
Sign up to set email alerts
|

Phase formation in molten system (Na/K)2O‐TiO2‐P2O5. Crystal structures of NASICON and langbeinite‐related phosphates (K/Na)1+xTi2(PO4)3 (x = 0 and 0.357)

Abstract: Crystallization of high temperature self-flux of system Na 2 O-K 2 O-TiO 2 -P 2 O 5 was investigated at different molar ratios (Na+K)/P = 0.9; 1.0 or 1.2 and Na/K = 1.0 or 2.0 over the temperature range 1000-650°C. The conditions of formation of complex phosphates K 0.10 Na 0.90 Ti 2 (PO 4 ) 3 (NASICONrelated) and K 0.877 Na 0.48 Ti ІІІ 0.357 Ti ІV 1.643 (PO 4 ) 3 (langbeiniterelated) have been established. The new obtained compounds were investigated using FTIR-spectroscopy, powder and single crystal X-ray di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Analysis of previously reported results for the interaction of TiO 2 with mixed phosphate melts such as Na 2 O–K 2 O–P 2 O 5 showed that the formation of langbeinite‐related phosphate took place at molar ratios of (Na+K)/P=0.9 and Na/K=1.0 . Structure determination of K 0.877 Na 0.48 Ti III 0.357 Ti IV 1.643 (PO 4 ) 3 showed partial substitution of K + by Na + and the formation of vacancies in the crystallographic positions of the alkaline metals . This latter fact significantly complicates estimation of the possibility to substitute potassium by sodium in the langbeinite‐related structure.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Analysis of previously reported results for the interaction of TiO 2 with mixed phosphate melts such as Na 2 O–K 2 O–P 2 O 5 showed that the formation of langbeinite‐related phosphate took place at molar ratios of (Na+K)/P=0.9 and Na/K=1.0 . Structure determination of K 0.877 Na 0.48 Ti III 0.357 Ti IV 1.643 (PO 4 ) 3 showed partial substitution of K + by Na + and the formation of vacancies in the crystallographic positions of the alkaline metals . This latter fact significantly complicates estimation of the possibility to substitute potassium by sodium in the langbeinite‐related structure.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of previous results, the interactions of TiN with Na 2 O–K 2 O–P 2 O 5 melts were studied in this work at (Na+K)/P molar ratios ranging from 0.9 to 1.2 to identify a route to fabricate L‐KNTP solid solutions. To achieve competitive conditions for sodium and potassium in the self‐flux, two values of the initial Na/K ratio (1.0 and 2.0) and a fixed value of added TiN (3.0 wt %) were selected.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations